No Evidence for Ape Plasmodium Infections in Humans in Gabon - Délicat-Loembet, Lucresse (PLoS One, 2015)
African great apes are naturally infected by a multitude of Plasmodium species most of them recently discovered, among which several are closely related to human malaria agents. However, it is still unknown whether these animals can serve as source of infections for humans living in their vicinity. To evaluate this possibility, we analysed the nature of Plasmodium infections from a bank of 4281 human blood samples collected in 210 villages of Gabon, Central Africa. Among them, 2255 were detected positive to Plasmodium using molecular methods (Plasmodium Cytochrome b amplification). A high throughput sequencing technology (454 GS-FLX Titanium technology, Roche) was then used to identify the Plasmodium species present within each positive sample. Overall, we identified with confidence only three species infecting humans in Gabon: P. falciparum, P. malariae and P. ovale. None of the species known to infect non-human primates in Central Africa was found. Our study shows that ape Plasmodium parasites of the subgenus Laverania do not constitute a frequent source of infection for humans. It also suggests that some strong host genetic barriers must exist to prevent the cross species transmission of ape Plasmodium in a context of ever increasing contacts between humans and wildlife.